The impact of relationship marketing strategy on customer loyalty at Taming Sari Tower, Malacca / Nurhafizah Shahru Alzaman - Shahru Alzaman, Nurhafizah (Faculty of Business and Management, 2017)
This research title is “The Impact of Relationship Marketing Strategy on Customer Loyalty at Taming Sari Tower, Malacca”. There is only one purpose of this study which is to determine what the best strategy that can be related to relationship marketing strategies towards customer loyalty at Taming Sari Tower. Besides that, there are involved two variables which are independent variable and dependent variable. Next, the independent variables consist of four relationships marketing which are trust, commitment, communication and conflict handling. In order to completing this research, the hypothesis was been constructed and focus on the objective to determine whether there has significant relationship between those independent variable with dependent variable (customer loyalty). Meanwhile, there are 140 of customers at Taming Sari have participated in this study as a respondents. The methodology used for this research was primary and secondary data collection. For primary data, the researcher was used the method of questionnaire to obtained and collect the data or information of data has completed, the researcher will continue with the analyzing and interpret the result of the data. Hence, there are several method that will be used to analyzed the data which are normality data, reliability analysis, frequency analysis, descriptive testing, Pearson`s Correlation Coefficient testing and Multiple Regression method. The result of the correlation testing was shows that all of the independent variable is significant and moderate with the customer loyalty (dependent variable) at Taming Sari Tower in Malacca. Thus, for the multiple regressions analysis shown that the most significant and has proven that there the impact of relation marketing strategy on customer loyalty which is trust and commitment compared to communication and conflict handling clearly shows that both independent variables is a weak factor towards customer loyalty. For the hypothesis, there are only two of hypothesis which including trust and commitment is accepted while the communication and conflict handling is not accepted.